PAPR reduction using combination of SAS preprocessed and WHT precoding for MIMO system of FBMC/OQAM transceiver - A.Shaheen, Imad; Zekry, Abdelhalim; Newagy, Fatma; Ibrahim, Reem (International Journal of Engineering and Technology, 2018)
FBMC/OQAM is Filter Bank Multicarrier with Offset Quadrature Amplitude Modulation system characterized by bandwidth efficiency, high data rate and more immunity to fading channels However, the combination of FBMC/OQAM system with Multiple Input and Multiple Output (MIMO) technology will increase the capacity of the system which may be used as the best scheme for next wireless communication system 5G . Unfortunately, one of the major drawbacks of MIMO FBMC/OQAM system is its high peak to average power ratio (PAPR) of the transmitted signals, resulting in signal distortion and reduced system performance. This paper proposes a new PAPR reduction method for MIMO FBMC/OQAM system based on the iterative addition and subtraction of FBMC/OQAM symbols which is known as Successive Addition Subtraction (SAS) followed by the WHT precoding. Simulation results show that the proposed schemes can improve the performance of the transceiver.Â Â